Early COVID‐19 infection after lung transplantation. Issue 10 (11th June 2020) - Keller, Brian C.; Le, Anh; Sobhanie, Mahdee; Colburn, Nora; Burcham, Pamela; Rosenheck, Justin; Howsare, Molly; Ganapathi, Asvin M.; Atyia, Sara A.; Haden, Michael; Whitson, Bryan A.; Mokadam, Nahush A.; et al.
Abstract : COVID‐19, the clinical syndrome caused by the novel coronavirus, SARS‐CoV‐2, continues to rapidly spread, leading to significant stressors on global healthcare infrastructure. The manifestations of COVID‐19 in solid organ transplant recipients are only beginning to be understood with cases reported to date in transplant recipients on chronic immunosuppression. Herein, we report the first case of COVID‐19 in a lung transplant recipient in the immediate posttransplant period, and we describe the epidemiologic challenges in identifying the source of infection in this unique situation. Abstract : COVID‐19 early after lung transplantation presents unique epidemiological and clinical management challenges.